2017
DOI: 10.1177/0192513x17746709
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Pathways Into and Impacts of Family Homelessness

Abstract: Homelessness has consequences for families, including risk of deterioration in the health of their members, disruption of family dynamics, and separation of parents and children. This study used qualitative interviews to explore pathways into and perceived consequences of homelessness among 18 families living in an emergency family shelter system in Canada. Findings showed that families’ experiences prior to their homelessness were characterized by vulnerability, instability, and isolation. In the emergency sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Concerning the research design, the studies are mostly qualitative in nature [15,25,34,35,[38][39][40]42].…”
Section: Results Of the Extracted Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the research design, the studies are mostly qualitative in nature [15,25,34,35,[38][39][40]42].…”
Section: Results Of the Extracted Datamentioning
confidence: 99%
“…Regarding the CONQual results, most of the selected studies obtained a moderate score [37][38][39][40]42], four reached a high score [15,25,34,36], one obtained a low score [35], and one achieved a very low score [41]. Despite their low classification, these last two articles were not eliminated, because their findings were unique and contributed to the knowledge of the phenomenon.…”
Section: Q1mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, focus groups with homeless women veterans identified a constellation of contributors to homelessness both related and not related to military service, including unemployment, relationship problems, and lack of social support . Qualitative research with homeless families in Canada and homeless adults in England also identified limitations in social support and relationship breakdown as central in pathways to homelessness . Another study, of drug users in Connecticut, found that personal factors including lack of social support and substance use interacted with structural factors such as lack of housing subsidies to contribute to homelessness …”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of interrelated factors that may lead to homelessness, qualitative research is particularly well suited to exploring pathways to homelessness. There has been little prior qualitative research, however, that has specifically examined reasons for and precipitants of homelessness in the words of people who have been affected by it . Further, to our knowledge no prior research has examined pathways to homelessness among ED patients, a potentially unique group.…”
mentioning
confidence: 99%